Molecular cloning, expression and functional analysis of a predicted HdiQM gene in small abalone, Haliotis diversicolor. (6th June 2015) - Wei‐Dong, Li; Xiang‐Min, Li; Ming‐Hui, Shen; Wen‐Gang, lü; Rong‐Xia, Wang; Min, Huang; Cai‐Huan, Ke
Abstract: The small abalone ( Haliotis diversicolor ) is a mollusc and was cultured in south of china. Problems such as the decreasing pathogen‐resistance and their mass mortality during the summer. The increased immunity of small abalone populations is a key factor in resolving these problems. Thus, the study of immunity‐related genes in small abalone has become important. In this study, three bacterial species were initially isolated from small abalone carcasses. The regression of infection was analysed, which revealed that the bacteria species could cause rapid morbidity in small abalone. A QM ‐like gene ( HdiQM ) was found and bacterial challenge tests showed that HdiQM gene expression was induced by the bacterial isolates from small abalone carcasses. Therefore, our results implied that HdiQM was found to be an inflammatory stress‐inducible gene associated with pathogen infection, with important functions in small abalone immunity.